Технологія підготовки кваліфікованих арбітрів із волейболу до змагальної діяльності та шляхи її оптимізації - Медвідь, Михайло Михайлович; Medvid, Mykhaylo (Східноєвропейський національний університет імені Лесі Українки, 2018)
Критерії якості та вимоги до кваліфікованої роботи суддів із волейболу набувають особливої значущості з урахуванням загальної інформатизації суспільства, що потребує перегляду підходів до підготовки арбітрів і пошуку нових форм для вдосконалення якості обслуговування матчів. Особливо це стосується офіційних змагань національного й міжнародного рівнів – чемпіонатів і Кубків країни, Європи, світу, Ігор Олімпіад, що підкреслює актуальність та своєчасність дослідження. Мета статті – розробити технологію підготовки кваліфікованих арбітрів із волейболу з урахуванням сучасних тенденцій розвитку виду спорту. Методи дослідження – аналіз науково-методичної літератури й даних мережі «Інтернет», контент- аналіз, методи інтерв’ю та бесіди, педагогічне спостереження. Результати роботи. Аналіз навчально- методичної літератури підтвердив гіпотезу щодо необхідності змін у підходах до професійної підготовки суддів з урахуванням сучасних вимог до інтерпретації офіційних правил змагань і методики суддівства відповідно до світових стандартів. Представлено розроблену структуру технології підготовки суддів із волейболу в Україні на основі врахування організаційних складових навчально-підготовчого процесу, необхідних видів підготовки, структурних компонентів реалізації планового підходу до набуття теоретичних знань, методичних навичок і практичного досвіду, точок контролю за ходом удосконалення суддівської майстерності та її ефективної реалізації в змагальному процесі. Висновок. Узагальнення результатів, отриманих у ході дослідження, надало підстави розробити структуру технології підготовки суддів із волейболу в Україні з урахуванням сучасних тенденцій розвитку виду спорту, організаційних, теоретичних, навчально-методичних і практичних компонентів, що забезпечують повноцінний та цілісний обсяг знань, умінь і навичок для планової роботи з підготовки кваліфікованих арбітрів різних кваліфікаційних категорій. The quality criteria and requirements for qualified volleyball referees’ work are of particular importance taking into account the general informatization of the society, which requires a review of approaches to the preparation of referees and the search for the new forms of match maintenance quality improvement. Especially it concerns official competitions of national and international levels – championships and Cups of the country, European and world championships, Olumpic Games, which emphasizes the relevance and timeliness of the study. Research methods – analysis of scientific and methodical literature and data from the Internet, content analysis, interview and conversation methods, pedagogical observation. The Results of the Work. Analysis of educational and methodical literature confirmed the hypothesis regarding the need for changes in the approaches to the professional training of referees, taking into account the modern requirements for the interpretation of the official rules of the competition and the methodology of refereeing in accordance with the international standards. The objective is to develop the technology for training qualified volleyball referees taking into account current trends in the development of the sport. Research methods – analysis of scientific and methodical literature and data from the Internet, content analysis, interview methods and conversations, pedagogical observation. The Results of the Work. The analysis of educational and methodical literature confirmed the hypothesis regarding the need for changes in the approaches to the professional training of judges, taking into account the modern requirements for the interpretation of the official rules of the competition and the methodology of refereeing in accordance with international standards.The developed structure of the technology of volleyball referees training in Ukraine is presented on the basis of the organizational components of the training process, the necessary types of training, structural components of the implementation of the planned approach to the acquisition of theoretical knowledge, methodological skills and practical experience, control points in the course of improving judicial skills and its effective implementation in the competitive process. Conclusions. Summarizing the results obtained in the course of the study allows developing the structure of volleyball referees training technology in Ukraine, taking into account modern trends in the development of the sport, organizational, theoretical, educational and methodical and practical components that provide a complete and comprehensive amount of knowledge and skills for the planned work on the preparation of qualified referees of various qualification categories.
Technologies for Qualified Volleyball Referees Training for Competitive Activities and Ways of its Optimization
Keywords: волейбол; арбітр; суддівство; технологія підготовки; оптимізація; volleyball; referee; refereeing; preparation technology; optimization